GAMIFICATION IN LANGUAGE TEACHING: A STRATEGY TO IMPROVE ENGAGEMENT AND PERFORMANCE IN SECONDARY SCHOOLS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This study explores the use of gamification as an innovative strategy to enhance student engagement and academic performance in language teaching within secondary schools. By integrating game elements such as points, badges, leaderboards, and interactive challenges into language lessons, teachers can create a motivating and immersive learning environment. The research investigates the impact of gamified instruction on students’ participation, motivation, and language proficiency development. Data collected from classroom observations, student surveys, and performance assessments indicate that gamification not only increases enthusiasm for learning but also fosters deeper understanding and retention of language skills. The findings suggest that gamification is a valuable pedagogical tool that can transform traditional language classrooms and improve educational outcomes for secondary school learners.